LC_Glucose-Inhibited Division Protein Is Required for Motility, Biofilm Formation, and Stress Response in Lysobacter capsici X2-3 - Zhao, Dan; Wang, Hong; Li, Zhiyuan; Han, Shengnan; Han, Chao; Liu, Aixin (Frontiers in Microbiology, 2022)
Glucose-inhibited division protein (GidA) plays a critical role in the growth, stress response and virulence of bacteria. However, how gidA may affect plant growth-promoting bacteria (PGPB) is still not clear. Our study aimed to describe the regulatory function of the gidA gene in Lysobacter capsici, which produces a variety of lytic enzymes and novel antibiotics. Here, we generated an LC_GidA mutant, MT16, and an LC_GidA complemented strain, Com-16, by plasmid integration. The deletion of LC_GidA resulted in an attenuation of the bacterial growth rate, motility and biofilm formation of L. capsici. Root colonization assays demonstrated that the LC_GidA mutant showed reduced colonization of wheat roots. In addition, disruption of LC_GidA showed a clear diminution of survival in the presence of high temperature, high salt and different pH conditions. The downregulated expression of genes related to DNA replication, cell division, motility and biofilm formation was further validated by RT–qPCR. Together, understanding the regulatory function of GidA is helpful for improving the biocontrol of crop diseases and has strong potential for biological applications.